SURXONDARYO VILOYATI ISHLAB CHIQARISH SANOAT RAQOBATBARDOSHLIGINI KOʻRSATKICHLAR STATISTIK TADQIQOTI (Marketing Journal, 2026)
AbstractThis article evaluated the competitiveness of industrial enterprises in theSurkhandarya region using economic and statistical methods. The study analyzed thevolume of industrial production, development dynamics, and the region’s share in thetotal industrial output of the country. Competitiveness was assessed using the industrialproduction index, labor productivity index, and an integrated competitiveness index.Statistical data for the period 2014-2024 were examined to identify growth rates andstructural characteristics of regional industry. The analysis showed steady growth ofindustrial production in absolute terms, while the share of the region in nationalindustrial output remained relatively low. The results indicated the need for industrialdiversification, development of innovative production activities, and improvement oflabor productivity to strengthen regional industrial competitiveness.Keywords: Surkhandarya region, industrial enterprises, competitiveness,industrial production, labor productivity, integrated index, economic and statisticalanalysis.